Properties of a chemical agents study of the Bayaldyr tailing dams lead – zinc oresspoil dump (International Journal of Biology and Chemistry, 2015)
With the development of mining and metallurgical industries on a soil surface there is a constant accumulation of technogenic waste from processing of minerals. These include tailing, sludges, slags and other substandard varieties of mineral resources. These elements of human origin can reach high local concentrations, in some cases up to toxic or scatter over large aqueous spaces or air currents. Thus the aim of the current research was to study the properties of a chemical agents of the Bayaldyr tailing dams lead – zinc oresspoil dump.